Dinamica del bosque secundario en agricultura de tumba y quema: interacciones entre tipos de uso dela tierra en la Amazonia peruana - Smith, J.; Kop, P. van de; Reategui, K.; Lombardi, I.; Sabogal, C.; Díaz, A. (2000)
The regeneration of secondary forests (SF) is a promising development within the generally pessimistic scenario of tropical deforestation. The objective of this paper was to document the regeneration of SF in slash and burn agriculture and to develop policy and technological recommendations for conserving forest cover on small farms and improve farmer welfare. Results confirmed that substantial areas of SF exist on slash and burn farms during the first few decades after settlement. As a result, over a third of the farm area is under the forest cover. This implies that deforestation in slash and burn farming may be less than previously believed. Soil recuperation is the most important reason for the existence of SF in slash and burn agriculture. The conclusion is that improved short-rotation fallows may recuperate the soil at the expense of forest cover, particularly in areas where most forest cover consists of SF.